2017
DOI: 10.1016/j.acvd.2017.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Right ventricular strain in heart failure: Clinical perspective

Abstract: The number of studies demonstrating the importance of right ventricular remodelling in a wide range of cardiovascular diseases has increased in the past two decades. Speckle-tracking imaging provides new variables that give comprehensive information about right ventricular function and mechanics. In this review, we summarize current knowledge of right ventricular mechanics in heart failure with reduced ejection fraction and preserved ejection fraction. We searched PubMed, MEDLINE, Ovid and Embase databases for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 45 publications
1
36
0
2
Order By: Relevance
“…Our subgroup analysis showed that patients using beta blockers had reduced RV systolic contractility compared to patients not using them. This latter finding could be secondary to negative inotropic effects of beta blockers and can offer a mechanistic explanation for the harm associated with beta blockers in patients with severe CLD, since reduction of RV contractility is associated with adverse cardiovascular outcomes in other cardiovascular disorders such as congestive heart failure . However, it must be reminded that patients treated with beta blockers could have additional unaccounted‐for factors (such as the presence of portal hypertension or more severe CLD) that can affect RV contractility, and the clinical importance of reduced RV strain in patients with CLD is unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our subgroup analysis showed that patients using beta blockers had reduced RV systolic contractility compared to patients not using them. This latter finding could be secondary to negative inotropic effects of beta blockers and can offer a mechanistic explanation for the harm associated with beta blockers in patients with severe CLD, since reduction of RV contractility is associated with adverse cardiovascular outcomes in other cardiovascular disorders such as congestive heart failure . However, it must be reminded that patients treated with beta blockers could have additional unaccounted‐for factors (such as the presence of portal hypertension or more severe CLD) that can affect RV contractility, and the clinical importance of reduced RV strain in patients with CLD is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…This latter finding could be secondary to negative inotropic effects of beta blockers and can offer a mechanistic explanation for the harm associated with beta blockers in patients with severe CLD, since reduction of RV contractility is associated with adverse cardiovascular outcomes in other cardiovascular disorders such as congestive heart failure. 31 However, it must be reminded that patients treated with beta blockers could have additional unaccounted-for factors (such as the presence of portal hypertension or more severe CLD) that can affect RV contractility, and the clinical importance of reduced RV strain in patients with CLD is unclear. Neither the design nor the power of this study was adequate to make a detailed analysis of coexisting conditions or outcomes, so these findings must be regarded as hypothesis generating rather than definite.…”
Section: Discussionmentioning
confidence: 99%
“…RVFWS is feasible in 88% to 94% of patients (24). The RVFWS's coefficients of variation for intraobserver and interobserver variability were 2-7% and 3-10%, respectively (24).…”
Section: Right Ventricle: Echocardiography A)diameter Measurementmentioning
confidence: 98%
“…The 2015 guideline about cardiac chamber quantification reported RVFWS mean (SD) value as −29.0(4.5)% with abnormality threshold of > −20 (13). RVFWS is feasible in 88% to 94% of patients (24). The RVFWS's coefficients of variation for intraobserver and interobserver variability were 2-7% and 3-10%, respectively (24).…”
Section: Right Ventricle: Echocardiography A)diameter Measurementmentioning
confidence: 99%
“…It provides a sensitive and rapid measure of segmental, mechanical changes within the RV as well as global longitudinal RV function. 30 Evaluation of the RV is performed in a two-chamber view. Speckle tracking is an angle-independent method, which is based upon routine 2D images.…”
Section: Echocardiographymentioning
confidence: 99%